Determination of N-Acetylcysteine by Cyclic Voltammetry Using Modified Carbon Paste Electrode with Copper Nitroprusside Adsorbed on the 3-Aminopropylsilica - de Sa, Acelino Cardoso [UNESP]; Paim, Leonardo L. [UNESP]; Bicalho, Urquisa de Oliveira; do Carmo, Devaney Ribeiro [UNESP] (Electrochemical Science Group, 2011)
Copper nitroprusside was formed on aminopropylsilica silica gel (3-AS) surface (SiCuNP) previously prepared following two steps. These materials were thoroughly characterized by Infrared (FTIR) and cyclic voltammetry. The above techniques confirmed the successful formation of the copper nitroprusside on the silica surface. The cyclic voltammogram of CuNPSD were found to exhibit two redox couples with (E(theta)')(1) = 0.34 V; (E(theta)')(2) = 0.76 V vs. Ag/AgCl, KCl((sat)) (KCl = 1.0 mol L(-1); v = 20 mV s(-1)) attributed to the redox processes Cu((I))/Cu((II)) and Fe((II))(CN)(5)NO/Fe((III))(CN)(5)NO respectively. The second redox process ((E(theta)') 2 presented by the graphite paste electrode with SiCuNP shows electrocatalytic activity for the oxidation of N-acetylcysteine. The linear range for the determination of N-acetylcysteine was found between 9.9 x 10(-5) and 8.9 x 10(-4) mol L(-1) showing a detection limit of 4.18 x 10(-5) mol L(-1) and an amperometric sensitivity of 3.02 x 10(-2) A /mol(-1) L.
Keywords: 3-aminopropylsilica Copper; Nitroprusside; Spectroscopy Cyclic Voltammetry; Carbon Paste Electrode, N-aceltylcysteine